Do communication and social interaction skills differ across youth diagnosed with autism spectrum disorder, attention-deficit/hyperactivity disorder, or dual diagnosis?. (December 2015) - Salley, Brenda; Gabrielli, Joy; Smith, Catherine M.; Braun, Matthew
Highlights: We examine ADOS communication/social interaction scores in youth with ASD and/or ADHD. Differences in ADOS scores differentiate diagnostic groups (ASD, ADHD, ASD + ADHD). Results provide support for utility of ADOS differential and co-occurring diagnosis. Abstract: Given the well-documented symptom overlap between autism spectrum disorder (ASD) and attention deficit/hyperactivity disorder (ADHD), careful evaluation of potential differentiation and overlap is critical for accurate diagnostic decisions. Although research has considered the use of symptom checklists and parent/teacher report questionnaires for symptom differentiation, standardized observational methods, typically utilized in the context of ASD evaluation, have received less attention. The present study examined the continuum of communication and social interaction impairment for youth diagnosed with ASD and ADHD, as indexed by the Autism Diagnostic Observation Schedule (ADOS). Participants were 209 youth ages 3–18 years with ASD, ADHD, dual diagnosis (ASD + ADHD) or no diagnosis. Differences across diagnostic groups were observed for mean communication and social interaction total scores on the ADOS, with the highest scores (i.e., greater impairment) observed for the ASD group and lowest scores for the ADHD and no diagnosis groups. Results provide the first evidence for use of the ADOS for distinguishing youth who have ADHD alone versus ASD alone or co-occurring ASD + ADHD. Findings are discussed in light of implications for clinical practice and future research.